Emergency psychiatric care seeking among individuals who died by suicide in Fortaleza in 2022 - Ana Carolina Parahyba Asfor; Matias Carvalho Aguiar Melo (Brazilian Journal of Psychiatry)
Objective: Suicide represents 1% of all deaths in the world, and it is more prevalent in developing countries. Because suicide mortality has been growing in recent years in Brazil, we investigated whether patients who committed suicide in 2022 in Fortaleza sought care in the state’s only psychiatric emergency service before the act. Methods: This retrospective cross-sectional study used data from electronic psychiatric emergency records and reports from the state department of forensics. Results: A total of 292 deaths (25% women) were identified, representing almost 2% of mortality in Fortaleza that year. Only 2.7% of those who committed suicide during this period requested an emergency psychiatric evaluation in the 3 months prior to death. Of these individuals, 75% mentioned suicidal ideation. Most deaths (70%) were due to hanging. Conclusion: The majority of patients who committed suicide in Fortaleza in 2022 did not seek care from the psychiatric emergency service prior to the event; further studies are needed to investigate the causes of this behavior.